Integrating Task-Based Language Teaching with Digital Tools to Enhance Writing Skills in EFL Classrooms: A Systematic Literature Review - Ilham (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study is a systematic literature review on the integration of Task-Based Language Teaching (TBLT) with digital tools to improve EFL students' writing skills. This approach is considered to encourage authentic language use, cognitive and affective engagement in writing learning. This review analyzed empirical studies from Scopus, DOAJ, and Google Scholar published between 2016-2025, with groupings based on themes, strategies, and challenges found. Results show that the integration of TBLT and digital technology significantly improves grammatical accuracy, vocabulary development, paragraph structure and text coherence. In addition, this approach also supports collaborative learning, creativity and digital literacy. However, challenges such as lack of teacher training, infrastructure limitations and students' digital competency gaps remain obstacles. The studies recommend continuous training, increased access to technology and mentoring programs as solutions. The findings emphasize the importance of systemic support, pedagogical adaptation and long-term research to ensure effective and sustainable implementation of digital-based TBLT.